Pharmacists' Efforts in Community Pharmacy to Achieve Health Protocol Compliance During the Covid-19 Pandemic in Lamongan - Primanitha Ria Utami; Siti Sholikhah; Aulia Kurnianing Putri; Devi Ristian Octavia; Emilia Rahmawati (Universitas STRADA Indonesia, 2021)
Pharmacists also play a role in helping control infections Covid-19, so this study aims to determine the efforts of Pharmacists in Community Pharmacy to achieve compliance with health protocols during the Covid-19 pandemic in Lamongan. This research is a descriptive observational study using a cross-sectional study with a validated questionnaire. There were 52 Pharmacists who practice at the Apothecaries. The results showed that most of the pharmacists made efforts such as: providing hand washing facilities(78.8%),preparing personal protective equipment (75.0%) and procuring multivitamins, handsanitizers (71.1%). Other efforts that are quite important for pharmacists are reminding each other to comply with the Covid-19 protocol by always wearing a mask, washing hands regularly, checking body temperature, disinfection of rooms and tools that are prone to contact with other people. Based on this, it appears that the existence of pharmacists during this pandemic is quite large